Strategic disclosure and informed trading with short‐selling constraints - Kumar, Praveen; Langberg, Nisan; Sivaramakrishnan, Konduru (Contemporary Accounting Research, 2025)
Security prices are affected by information strategically disclosed by managers as well as by informed trading of outsiders and vice versa. However, market frictions, such as short‐selling costs and constraints, significantly affect trading in financial markets. In this article, we examine the joint determination of voluntary disclosure, security prices, and short‐selling, and address the following issues: How do major market frictions affect managerial disclosures? How do disclosures influence strategic informed trading in the presence of frictions? What does the interaction of strategic disclosure and informed trading imply for price efficiency? We find that short‐selling (trading) costs have a substantial impact on the equilibrium disclosure policy and its interaction with informed trading and price efficiency. Because of endogenously binding short‐sale constraints, better‐informed traders can either deter or encourage disclosure, thus reconciling mixed available evidence on the relation between short‐sale constraints and managerial disclosure. Furthermore, price efficiency need not improve with managers' information endowment because greater disclosure can endogenously inhibit informed short‐selling in equilibrium. Our analysis also generates novel empirical predictions relevant to the literature on managerial disclosure, shorting, and price efficiency.